Clinical characteristics and follow-up of complex arrhythmias associated with RYR2 gene mutations in children - Wang, Yefeng; Yang, Yufan; Xu, Ningan; Xiao, Yunbin; Zuo, Chao; Chen, Zhi (Frontiers in Genetics, 2024)
Clinical characteristics and follow-up of complex arrhythmias associated with RYR2 gene mutations in children Objective: The aim of this study was to analyze the diagnosis, treatment, and follow-up of six cases of complex arrhythmias associated with RYR2 gene mutations in children. Method: A retrospective analysis was conducted on six children diagnosed with complex arrhythmias associated with RYR2 gene mutations. The study included an analysis of the age of onset, initial symptoms, electrocardiographic characteristics, genetic results, treatment course, and follow-up outcomes. Results: Among the six cases included in the study, there were four males and two females, with an average age of 3.5 ± 0.5 years. The average time from initial symptoms to diagnosis was 2.7 ± 1.3 years. The most common clinical manifestation was syncope, with exercise and emotions being the main triggers. All six children had de novo missense mutations in the RYR2 gene identified through whole-exome sequencing. In Holter ECG, atrial arrhythmias and sinoatrial node dysfunction were commonly observed in younger children. Four patients underwent exercise stress testing, with two experiencing bidirectional ventricular premature contractions and two experiencing bidirectional ventricular tachycardia and polymorphic ventricular tachycardia. Initial treatment involved oral propranolol or metoprolol. If arrhythmias persisted, flecainide or propafenone was added as adjunctive therapy. Two patients received permanent cardiac pacemaker treatment (single chamber ventricular pacemaker, VVI). All patients survived, with three experiencing occasional syncope during treatment. The follow-up period ranged from 12 to 37 months, with an average follow-up time of 24.3 ± 3.7 months. Conclusion: Complex arrhythmias associated with RYR2 gene mutations in children can present with various clinical manifestations. Atrial arrhythmias combined with sinoatrial node dysfunction are commonly observed in younger children, and the combination of pharmacological therapy and cardiac pacemaker treatment yields favourable treatment outcomes.